Reactive Oxygen Species and Gibberellin Acid Mutual Induction to Regulate Tobacco Seed Germination - Zhan Li; Yue Gao; Yuchan Zhang; Cheng Lin; Dongting Gong; Yajing Guan; Jin Hu (Frontiers in Plant Science, 2018)
Seed germination is a complex process controlled by various mechanisms. To examine the potential contribution of reactive oxygen species (ROS) and gibberellin acid (GA) in regulating seed germination, diphenylene iodonium chloride (DPI) and uniconazole (Uni), as hydrogen peroxide (H2O2) and GA synthesis inhibitor, respectively, were exogenously applied on tobacco seeds using the seed priming method. Seed priming with DPI or Uni decreased germination percentage as compared with priming with H2O, especially the DPI + Uni combination. H2O2 and GA completely reversed the inhibition caused by DPI or Uni. The germination percentages with H2O2 + Uni and GA + DPI combinations kept the same level as with H2O. Meanwhile, GA or H2O2 increased GA content and deceased ABA content through corresponding gene expressions involving homeostasis and signal transduction. In addition, the activation of storage reserve mobilization and the enhancement of soluble sugar content and isocitrate lyase (ICL) activity were also induced by GA or H2O2. These results strongly suggested that H2O2 and GA were essential for tobacco seed germination and by downregulating the ABA/GA ratio and inducing reserve composition mobilization mutually promoted seed germination. Meanwhile, ICL activity was jointly enhanced by a lower ABA/GA ratio and a higher ROS concentration.